Cortical vessel sign on susceptibility weighted imaging reveals clinically relevant hypoperfusion in internal carotid artery stenosis - Mundiyanapurath, Sibu; Ringleb, Peter A.; Burth, Sina; Möhlenbruch, Markus Alfred; Floca, Ralf; Wick, Wolfgang; Bendszus, Martin; Radbruch, Alexander (European journal of radiology, 2016)
Background and purpose - Internal carotid artery (ICA) stenosis can lead to cerebral hypoperfusion and is a common cause of stroke. As susceptibility weighted imaging (SWI) has been used for penumbra imaging in acute ischemic stroke, we aimed at analyzing hypoperfusion using SWI in patients with ICA stenosis. - Material and methods - Clinical characteristics, asymmetric cortical vessel sign (more and/or larger, hypointense asymmetric cortical vessels) on SWI, Doppler sonography results and diffusion weighted imaging (DWI) lesion volume were retrospectively analyzed in patients with ICA stenosis. In a subgroup of patients, volume of prolonged time to peak and volume of prolonged time to peak of the residue curve (Tmax) were measured as reference standard. Outcome was assessed as modified Rankin score at discharge. - Results - 104 patients were included. Median age was 72 and median degree of stenosis 70% according to NASCET. 13% had a asymmetric cortical vessel sign. These patients had a higher degree of stenosis (80% vs. 70%, p=0.004), were more often symptomatic (93% vs. 61%, p=0.020) and had higher DWI volume (7.3ml vs. 0.2ml, p=0.011). Specificity for the prediction of DWI lesions was 86%. Also, patients with asymmetric cortical vessel sign had lower rates of favorable outcome (mRS=0-2; 57% vs. 82%, p=0.033) and volumes of Tmax≥4s, ≥6s, ≥8s, ≥10s and TTP≥2s, ≥4s, ≥6s were significantly higher. In multivariate analysis, asymmetric cortical vessel sign was an independent negative predictor of favorable outcome (mRS 0-2; OR 0.184; CI [0.039; 0.875] p=0.033). - Conclusion - In patients with ICA stenosis, asymmetric cortical vessel sign is a sign of clinically relevant hypoperfusion.